Bentuk Pertunjukan Dan Fungsi Kesenian Obrog-Obrog Di Desa Darmawangi Kecamatan Tomo Kabupaten Sumedang - Dicky Irwan Firmansyah (Paraguna, 2022)
This paper discusses the form and function of obrog-obrog art in Darmawangi Village, Tomo District, Sumedang Regency which is a typical art of the month of Ramadan. In practice, this art is highly anticipated by the community, because it plays an important role in the local community in deepening sahur and also other functions of entertainment, communication, movement response and cultural sustainability. The method used in this paper is a descriptive method with a paradigm approach based on the theory of performing arts by Hermin Kusmayanti, namely there are three phases of performing arts, namely form, meaning and function. In addition to the theory of performing arts, the theory of the function of music by Alan P. Merriam from his book entitled The Anthropology of Music is also used as a theoretical approach. The results of this study analyze the form of performance in the form of the structure and pattern of percussion of musical instruments and the function of obrog-obrog arts as a medium of entertainment, as communication, as a response to movement, and as cultural sustainability.